2014
DOI: 10.1177/0748175613505622
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Measure Student Use of Academic Success Skills

Abstract: This article describes the development of the Student Engagement in School Success Skills instrument including item development and exploratory factor analysis. The instrument was developed to measure student use of the skills and strategies identified as most critical for longterm school success that are typically taught by school counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…Scores on the total scale were distributed normally with a mean of 65.83 and a standard deviation of 15.44. Exploratory (Carey, Brigman, Webb, Villares, & Harrington, 2014) and confirmatory factor analyses (Brigman et al, 2015) indicated that the SESSS has three underlying factors relating to Self‐Direction of Learning, Support of Classmates Learning, and Self‐Regulation of Arousal. A study of the convergent and divergent validity of the SESSS survey (Villares et al, 2014) indicated that these subscales correlated highly with the MSLQ Cognitive Strategy Use and Self‐Regulation subscales but did not correlate with the MSLQ Test Anxiety subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Scores on the total scale were distributed normally with a mean of 65.83 and a standard deviation of 15.44. Exploratory (Carey, Brigman, Webb, Villares, & Harrington, 2014) and confirmatory factor analyses (Brigman et al, 2015) indicated that the SESSS has three underlying factors relating to Self‐Direction of Learning, Support of Classmates Learning, and Self‐Regulation of Arousal. A study of the convergent and divergent validity of the SESSS survey (Villares et al, 2014) indicated that these subscales correlated highly with the MSLQ Cognitive Strategy Use and Self‐Regulation subscales but did not correlate with the MSLQ Test Anxiety subscale.…”
Section: Methodsmentioning
confidence: 99%
“…For example,Walstad and Rebeck (2001) give the names and affiliations of all experts involved in the development of their "Test of Economic Literacy" (pp [3][4]68)…”
mentioning
confidence: 99%
“…The SESSS is a 33-item student self-report of cognitive engagement in SSS program skills and strategies, using language specific to the SSS curriculum, and takes approximately 15 minutes to complete (Carey, Brigman, Webb, Villares, & Harrington, 2013). Students are asked to circle how often they have engaged in a list of behaviors within the last 2 weeks (e.g., "I tried to encourage a classmate who was having a hard time doing something," "I noticed when another student was having a bad day," "I listened to music so that I would feel less stressed").…”
Section: Student Engagement In School Success Skills Surveymentioning
confidence: 99%
“…The SESSS is intended for use with students in grades 3-12. Though a four-factor model was first revealed in an exploratory factor analysis conducted by Carey et al (2013), a subsequent confirmatory factor analysis revealed the following three factors: selfdirection of learning (which represents the combination of two original factors-management of learning and application of learning strategies), support of classmates' learning and self-regulation of arousal, which correspond to the three subscales of the SESSS (Brigman et al, 2014). Coefficient alphas for the three SESSS subscales were as follows: self-direction of learning: 0.89, support of classmates' learning: 0.79 self-regulation of arousal: 0.68, and 0.90 for the SESSS as a whole , indicating good internal consistency.…”
Section: Student Engagement In School Success Skills Surveymentioning
confidence: 99%